The Decameron project : 29 new stories from the pandemic - LaValle, Victor D., 1972-; Awad, Mona; Shamsie, Kamila. 1973-; Tóibín, Colm, 1955-; Moore, Liz, 1983-; Orange, Tommy, 1982-; Slimani, Leïla, 1981-; Atwood, Margaret, 1939-; Li, Yiyun, 1972-; Keret, Etgar, 1967- (Scribner, 2020)
Presents a collection of short stories originally commissioned by "The New York Times Magazine" as the COVID-19 pandemic swept the world, from twenty-nine authors including Margaret Atwood, Tommy Orange, Edwidge Danticat, and more, in a project inspired by Boccaccio's "The Decameron."